Biosynthesis of Diterpenoids in Tripterygium Adventitious Root Cultures. Issue 1 (27th July 2017) - Inabuy, Fainmarinat S.; Fischedick, Justin T.; Lange, Iris; Hartmann, Michael; Srividya, Narayanan; Parrish, Amber N.; Xu, Meimei; Peters, Reuben J.; Lange, B. Markus
Abstract : Adventitious root cultures provide insights to elucidating the biosynthesis of pharmaceutically relevant diterpenoids in the model genus Tripterygium. Abstract: Adventitious root cultures were developed from Tripterygium regelii, and growth conditions were optimized for the abundant production of diterpenoids, which can be collected directly from the medium. An analysis of publicly available transcriptome data sets collected with T. regelii roots and root cultures indicated the presence of a large gene family (with 20 members) for terpene synthases (TPSs). Nine candidate diterpene synthase genes were selected for follow-up functional evaluation, of which two belonged to the TPS-c, three to the TPS-e/f, and four to the TPS-b subfamilies. These genes were characterized by heterologous expression in a modular metabolic engineering system in Escherichia coli . Members of the TPS-c subfamily were characterized as copalyl diphosphate (diterpene) synthases, and those belonging to the TPS-e/f subfamily catalyzed the formation of precursors of kaurane diterpenoids. The TPS-b subfamily encompassed genes coding for enzymes involved in abietane diterpenoid biosynthesis and others with activities as monoterpene synthases. The structural characterization of diterpenoids accumulating in the medium of T. regelii adventitious root cultures, facilitated by searching the Spektraris online spectral database, enabled us to formulate a biosynthetic pathway for the biosynthesis of triptolide, a diterpenoid with pharmaceutical potential. Considering the significant enrichment of diterpenoids in the culture medium, fast-growing adventitious root cultures may hold promise as a sustainable resource for the large-scale production of triptolide.